5(2a-1)=9(a-5)

Simple and best practice solution for 5(2a-1)=9(a-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2a-1)=9(a-5) equation:


Simplifying
5(2a + -1) = 9(a + -5)

Reorder the terms:
5(-1 + 2a) = 9(a + -5)
(-1 * 5 + 2a * 5) = 9(a + -5)
(-5 + 10a) = 9(a + -5)

Reorder the terms:
-5 + 10a = 9(-5 + a)
-5 + 10a = (-5 * 9 + a * 9)
-5 + 10a = (-45 + 9a)

Solving
-5 + 10a = -45 + 9a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-9a' to each side of the equation.
-5 + 10a + -9a = -45 + 9a + -9a

Combine like terms: 10a + -9a = 1a
-5 + 1a = -45 + 9a + -9a

Combine like terms: 9a + -9a = 0
-5 + 1a = -45 + 0
-5 + 1a = -45

Add '5' to each side of the equation.
-5 + 5 + 1a = -45 + 5

Combine like terms: -5 + 5 = 0
0 + 1a = -45 + 5
1a = -45 + 5

Combine like terms: -45 + 5 = -40
1a = -40

Divide each side by '1'.
a = -40

Simplifying
a = -40

See similar equations:

| -4y+4=-6y-6 | | 12x+6=54 | | 144-3x=5x-24 | | 9=5(2c-5) | | 2(x^2+14x-378)=0 | | 5x+2y=52 | | 9m+9=8m+5 | | -3=4N-(7) | | 3+3x-5=3x-2 | | 5x+3y=24 | | 5x-3y=26 | | x-6=6-9 | | -3=4n-7 | | -4(2x-20)+100=6x+800 | | 4x+3y+2=0 | | 8=5n-12 | | 8(x-2)=7x-20 | | 3n-1=-16 | | -2y-9=7y+9 | | 5x-2x+100=40+80 | | 5x+4=7x-20 | | 10x^2+6=20x | | x/3=33 | | 4u+5v-6(3u-4v)= | | -2x+4=35 | | -3(3x-27)=5x+29 | | (x^2)+2=0 | | 3x=87+x | | 4x+20=50-10 | | 33=6x+3x-x+9 | | 4x+4+2x=3x+1 | | X^2-3x+36=0 |

Equations solver categories